Synthesis and Bio-assay of Some 3-(2H-1,4-Benzothiazin-3-yl)-2-methylchromones - Prabha Sharma, Vinay (Asian Journal of Chemistry, 2016)
Some 3-(2H-1,4-Benzothiazin-3-yl)-2-methylchromones have been synthesized. Their structural assignments are made on the basis of elemental analysis and spectral characteristics. Tested compounds did not show any significant activity.